Transforming Pedagogy with Digital Games: Tapak Nusantara as a Tool for Early Childhood Critical Thinking Development - Kartika Rinakit Adhe; Mustaji Mustaji; Andi Kristanto; Suryanti Suryanti; Priyadarshini Muthukrishnan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study explores pedagogical transformation in early childhood education through digital game-based learning by developing Tapak Nusantara, a digital adaptation of the traditional crankle game. Integrating pedagogical principles in game-based learning is crucial for fostering critical thinking in young learners. This research bridges cultural pedagogy with digital learning, ensuring children acquire meaningful educational experiences while preserving Indonesian culture. Method: This research is development research with a 4D model approach. The subjects of this study were 53 children in IT Nada Ashobah kindergarten class B and Labschool Unesa kindergarten class B. Results: This study showed a significant difference between the crankle traditional and crankle traditional games. The results of this study showed a significant difference between the pre-test and post-test scores in both the Nada Ashobah IT Kindergarten (t = -8.494, p < 0.001) and Labschool (t = -5.783, p < 0.001) groups, which indicated the effectiveness of the game in improving children's critical thinking. Novelty: This research lies in three key contributions: (1) the pedagogical innovation of integrating game-base learning with cultural education, (2) the digital transformation of a traditional game into a developmentally appropriate learning tool, and (3) Tapak Nusantara representative culture, pedagogy, and technology to cultivate critical thinking for early childhood.